Metal gel composite osteochondral repair porous scaffold material based on heterogeneous double-layer bonding technology and preparation method of metal gel composite osteochondral repair porous scaffold material
Through heterobilayer bonding technology, metal gel composite osteocartilage repair porous scaffold material is prepared by using inorganic magnesium alloy and organic collagen, which solves the problem of osteocartilage heterostructure repair and achieves efficient osteocartilage regeneration and repair effects.
Patent Information
- Application Number
- CN202411221511.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art is difficult to effectively repair the heterostructure of osteocartilage, resulting in poor treatment effect, and conventional materials cannot meet the actual repair needs of osteocartilage, which is prone to develop into osteoarthritis.
Using inorganic metals and organic natural macromolecules as raw materials, metal gel composite osteocartilage repair porous scaffold material is prepared through heterogeneous double-layer bonding technology, and subchondral bone repair is performed using inorganic magnesium alloy porous scaffolds, and adding it to the upper layer to promote cartilage differentiation Growth factors to create a suitable physical and chemical microenvironment.
Efficient repair of osteocartilage defects is achieved, and the mechanical properties matching of inorganic magnesium alloy stents and the release of cartilage differentiation growth factors are promoted, which promotes the regeneration of cartilage and bone, and the material can be degraded in the body without secondary surgery.
Smart Images

Figure CN119158084A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation technology of a cartilage repair material, and in particular to a metal gel composite osteocartilage repair porous scaffold material based on a heterogeneous double-layer bonding technology and a preparation method thereof. Background Art
[0002] Osteochondral tissue is composed of cartilage and subchondral bone, which is easily damaged by traffic accidents, accidental trauma, etc. Since the upper cartilage and subchondral bone are two completely heterogeneous structures, the single strategy that can be used for bone repair or cartilage repair is often unable to achieve the ideal therapeutic effect. If the osteochondral defect is not treated, or the treatment effect is poor, it is easy to develop into osteoarthritis, which affects the patient's mobility and can even cause disability in severe cases. Therefore, the treatment of osteochondral has become a clinical problem that needs to be overcome in orthopedics.
[0003] Bone tissue engineering technology is an effective treatment for bone defects. In recent years, researchers have developed a variety of organic osteochondral repair materials with a double-layer structure, achieving some therapeutic benefits. However, the biochemical structure and mechanical properties of the upper and lower layers of osteochondral cartilage differ significantly. Simply selecting raw materials to create double-layered tissue engineering scaffolds and other materials cannot adequately meet the actual needs of osteochondral repair.
[0004] Therefore, to address the above-mentioned issues, the present invention, for the first time, selects inorganic metals and organic natural macromolecules as raw materials to prepare a metal gel composite osteochondral repair porous scaffold material with a heterogeneous double layer, and applies the most common bonding technology to the efficient bonding between the double layers. The lower layer of inorganic magnesium alloy porous scaffold is used for subchondral bone repair. Its mechanical properties are compatible, and the released magnesium ions have the function of promoting osteogenesis. The upper layer of organic gel scaffold uses collagen from the cartilage matrix component as raw material, and adds growth factors that promote cartilage differentiation, creating a physical and chemical microenvironment similar to that of the cartilage matrix. Through the efficient combination of the heterogeneous double layer structure, efficient repair of osteochondral defects can be achieved. Summary of the Invention
[0005] The present invention aims to address the problem that simply selecting raw materials to prepare tissue engineering scaffolds with a double-layer structure cannot effectively meet the actual needs of osteochondral repair. By providing a metal gel composite osteochondral repair porous scaffold material based on heterogeneous double-layer bonding technology and its preparation method, the material can effectively repair osteochondral defects through the efficient coordination of the heterogeneous double-layer structure.
[0006] The present invention is achieved by adopting the following technical solutions:
[0007] A method for preparing a metal gel composite osteochondral repair porous scaffold material based on heterogeneous double-layer bonding technology comprises the following steps:
[0008] 1) Using metal 3D printing technology to obtain a metal lower bracket;
[0009] 2) using a methacryloylation type I collagen (ColMA) / photoinitiator solution as a matrix, the matrix is mixed with a cartilage differentiation promoting growth factor and a nanocarrier loaded with the cartilage differentiation promoting growth factor, and 3D printing is performed to obtain an upper scaffold;
[0010] 3) polarizing the bonding surface of the lower scaffold using plasma surface activation technology, and then pre-wetting the bonding surfaces of the upper and lower scaffolds with a water-absorbing self-curing adhesive, wherein the bonding surface of the lower scaffold is coated with a PBS solution for wetting;
[0011] 4) Bonding the upper and lower scaffolds, and then aging the adhesive to obtain a metal gel composite osteochondral repair porous scaffold material based on heterogeneous double-layer bonding technology.
[0012] Furthermore, the metal lower layer support is an inorganic magnesium alloy porous lower layer support with a pore size of 250-350 microns; the upper layer support is an organic porous support with a pore size of 150-250 microns.
[0013] Furthermore, in step 1), during the metal 3D printing process, selective laser melting is used, the oxygen content in the printing cavity is less than 0.2%, and a magnesium alloy ball-milled powder with a particle size of 15-25 μm is added to the metal 3D printing device, and the laser beam spot diameter is set to 40-60 μm, the laser power is 400-600 W, the scanning rate is 400-800 mm / s, the scanning spacing is 80-120 μm, the nozzle diameter is 30-40 μm, the nozzle movement rate is 3-6 mm / s, the injection frequency is 0.5-2 kHz, and the print layer thickness is 40-60 μm; after printing is completed, it is heated to 500-550 ° C at a heating rate of 10-20 ° C / min and sintered for 2-3 hours, and cooled to 35-40 ° C at a cooling rate of 5-10 ° C / min.
[0014] Furthermore, in step 2) preparing the ColMA / photoinitiator solution, the degree of substitution of ColMA is 60-90%, the concentration is 10-20 wt%, the photoinitiator is one of LAP, Irgacure, and photoinitiator 2959, the concentration is 0.15-0.3 wt%, and the solvent is PBS;
[0015] The cartilage differentiation promoting growth factors are one or more of GDF-5, bFGF, FGF-10, Afgf and EGF, wherein the concentration of the cartilage differentiation promoting growth factors directly mixed in the matrix is 160-220 μM, and the concentration of the cartilage differentiation promoting growth factors in the nanocarrier is 600-800 μM;
[0016] The concentration of the nanocarrier loaded with the cartilage differentiation promoting growth factor in the matrix is 0.05-0.1 wt %.
[0017] Furthermore, in step 2), during the preparation of the nanocarrier loaded with the growth factor promoting cartilage differentiation, an ultrasonic loading method is used, with an ultrasonic power of 100-180 W, a temperature of 4-10° C., a time of 5-15 min, and a nanocarrier concentration of 0.1-0.5 wt %. After loading, the nanocarrier is freeze-dried;
[0018] The nanocarrier is one or more of ZIF-8, mesoporous manganese dioxide and mesoporous silica, preferably mesoporous silica.
[0019] Furthermore, in step 2), during the 3D printing process, light-proof conditions are adopted, the nozzle aperture is 200-400 microns, the printing speed is 20-25 mm / s, the printing accuracy in the XY axis direction is 0.005-0.01 mm, the accuracy in the Z axis direction is 0.002-0.004 mm, the printing temperature is 30-35°C, the UV wavelength is 405 nm, the power is 20-40 W, and the curing time is 5-10 min.
[0020] Furthermore, in step 3) the plasma surface activation process, nitrogen is used as the plasma gas, the nitrogen gas flow rate is 2.5-4.5 L / min, the power is 200-450 W, the output frequency is 25-45 kHz, the distance between the device and the sample is maintained at 15-25 mm, and the processing time is 5-15 min;
[0021] The bonding surfaces are respectively the lower surface of the upper support and the upper surface of the lower support;
[0022] The water-absorbing self-curing adhesive is composed of polyethyleneimine and polyacrylic acid, with an addition amount of 50-100 mg / cm 2 ;
[0023] The pre-wetting time is 10-20s.
[0024] Furthermore, in step 4), when bonding the upper and lower brackets, they need to be pressed to make them tightly bonded, and the bonding time is 5-15 minutes; during the aging process, the temperature is 4-10° C., and the aging time is 40-80 minutes.
[0025] A metal gel composite osteochondral repair porous scaffold material based on heterogeneous double-layer bonding technology is obtained by the preparation method according to any one of claims 1 to 8.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] 1) The present invention uses magnesium alloy, ColMA, cartilage differentiation-promoting growth factors, water-absorbing self-curing adhesives, etc. as raw materials, and combines 3D printing, metal 3D printing, nanocomposite, plasma surface activation, adhesive bonding and other combined processes to produce a metal gel composite osteochondral repair porous scaffold material based on heterogeneous double-layer bonding technology. The above raw material selection and process combination are original to the present invention.
[0028] 2) This invention innovatively proposes an organic-inorganic biphasic heterogeneous bilayer porous scaffold material strategy for bone and cartilage repair. This strategy involves bonding an inorganic magnesium alloy porous scaffold to an organic ColMA porous scaffold using a water-absorbing self-curing adhesive. The magnesium alloy scaffold is used for subchondral bone repair, while the ColMA scaffold loaded with cartilage growth factor is used for cartilage repair. The density and elastic modulus of the inorganic magnesium alloy scaffold are close to those of human bone tissue, and it has good bioactivity and osteoconduction ability. The weakly alkaline environment generated by degradation in the body and the Mg 2+ It has osteoinductive properties; collagen is an important component of the natural cartilage matrix. ColMA and growth factors that promote cartilage differentiation together provide a physical and chemical microenvironment suitable for cartilage repair, effectively promoting the repair of cartilage defects. The two are bonded together using a water-absorbing self-curing adhesive, achieving an organic composite between the organic and inorganic phases.
[0029] 3) The present invention combines the structural characteristics and manufacturing process requirements of the metal gel composite osteochondrocyte repair porous scaffold material based on heterogeneous double-layer bonding technology to cleverly realize new applications of 3D printing, metal 3D printing, nanocomposite, plasma surface activation, adhesive bonding and other processes. First, 3D printing, metal 3D printing and nanocomposite are used to respectively prepare two organic and inorganic porous scaffold materials, and a cartilage differentiation-promoting growth factor with a timed release function is loaded in the organic scaffold; secondly, since the direct bonding effect between the water-absorbing self-curing adhesive and the magnesium alloy is poor, we cleverly introduce plasma surface activation technology to polarize the magnesium alloy bonding surface and introduce polar functional groups to improve the interfacial bonding strength. Moreover, after pre-impregnation of the two scaffold materials with the adhesive, further bonding and aging are carried out to obtain the optimal bonding strength, thereby ensuring the stability between the organic and inorganic phases. Although the above-mentioned processes have been applied individually in this field or other fields, the present invention is able to realize the preparation of metal gel composite bone cartilage repair porous scaffold materials based on heterogeneous double-layer bonding technology through the organic synergy between the above-mentioned combined processes, which has the obvious characteristics of new application of old processes and synergistic efficiency.
[0030] 4) The metal gel composite osteochondrocyte repair porous scaffold material based on heterogeneous double-layer bonding technology in the present invention has the functions of inducing cell growth, promoting osteochondrocyte repair, and self-degradation in vivo. The pore size of the lower magnesium alloy scaffold is 250-350μm, which is consistent with the structural characteristics of trabecular bone and can promote bone ingrowth; the pore size of the upper ColMA scaffold is 150-250μm, which can better promote the adhesion and proliferation of chondrocytes, and can efficiently induce bone repair and cartilage repair cells to grow into the pores of the scaffold. Secondly, the weak alkaline environment generated by the degradation of the lower magnesium alloy scaffold in the body and the Mg 2+ It has osteoinductive properties and can effectively promote the repair of subchondral bone. The upper layer of the ColMA scaffold is directly and evenly mixed with cartilage differentiation growth factors and nanofillers loaded with cartilage differentiation growth factors. The directly mixed cartilage differentiation growth factors have a faster release rate, which can promote early cartilage differentiation. However, the cartilage differentiation growth factors loaded within the nanofillers have a slower release rate due to the physical steric hindrance of the fillers, which can serve the later stages of cartilage differentiation. The sequential release of cartilage differentiation growth factors through these two loading methods, combined with the physical three-dimensional microenvironment provided by ColMA, can effectively achieve cartilage regeneration and repair. Furthermore, both processes use biodegradable raw materials, which can be degraded during the treatment of osteochondral defects, eliminating the need for secondary surgery.
[0031] 5) The present invention can combine MRI, CT and other technologies to comprehensively judge the patient's osteochondral defect, and through the design of drawings before 3D printing, jointly determine the thickness of the upper and lower layer structures of the metal gel composite osteochondral repair porous scaffold material based on heterogeneous double-layer bonding technology, thereby obtaining a heterogeneous double-layer scaffold material adapted to each patient. This technology is customizable and can meet the different needs of different patients. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the preparation process of the metal gel composite osteochondral repair porous scaffold material based on the heterogeneous double-layer bonding technology of the present invention;
[0033] Figure 2 This is an embodiment of the present invention based on the magnesium ion release curve of the metal gel composite osteochondrocyte repair porous scaffold material based on the heterogeneous double-layer bonding technology (Example 1);
[0034] Figure 3 This is a diagram showing the effect of the metal gel composite osteochondral repair porous scaffold material on osteochondral defects based on heterogeneous double-layer bonding technology in an embodiment of the present invention (a corresponds to Example 1, b corresponds to Example 2). DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0036] Comparative Example 1:
[0037] Magnesium alloy ball-milled powder with a particle size of 15 μm was added to the metal 3D printing device, and the laser beam spot diameter was set to 40 μm, the laser power was 400 W, the scanning rate was 600 mm / s, the scanning spacing was 100 μm, the nozzle diameter was 30 μm, the nozzle movement rate was 4 mm / s, the injection frequency was 1 kHz, the printing layer thickness was 40 μm, and the inorganic magnesium alloy porous scaffold with a pore size of 300 microns was produced by metal 3D printing technology; after printing, it was heated to 500 ° C at a heating rate of 10 ° C / min and sintered for 3 hours, and then cooled to 40 ° C at a cooling rate of 5 ° C / min.
[0038] After irradiation sterilization, the above-mentioned scaffold material was implanted into a rabbit articular osteochondral defect model to further observe the osteochondral repair.
[0039] After the above-mentioned scaffold material was irradiated and sterilized, it was implanted into a rabbit articular bone and cartilage defect model. After 8 weeks, the sample as a whole had an osteogenesis effect. The CT results showed that new bone regeneration was achieved in the defect area, and no cartilage formation was observed.
[0040] Example 1:
[0041] 1) Add magnesium alloy ball-milled powder with a particle size of 15 μm into the metal 3D printing device, set the laser beam spot diameter to 40 μm, the laser power to 400 W, the scanning rate to 600 mm / s, the scanning spacing to 100 μm, the nozzle diameter to 30 μm, the nozzle movement rate to 4 mm / s, the injection frequency to 1 kHz, the printing layer thickness to 40 μm, and the inorganic magnesium alloy porous lower layer support with a pore size of 300 microns by metal 3D printing technology; after printing, heat to 500 ° C at a heating rate of 10 ° C / min and sinter for 3 h, and cool to 40 ° C at a cooling rate of 5 ° C / min.
[0042] 2) Using ColMA with a degree of substitution of 60%, a 10 wt% ColMA / photoinitiator solution (the photoinitiator is LAP, with a concentration of 0.20 wt%) was prepared, into which the chondrogenic differentiation growth factor GDF-5 and the mesoporous silica loaded with the chondrogenic differentiation growth factor GDF-5 were mixed directly in the ColMA matrix at a concentration of 200 μM; the method for loading the osteogenic differentiation factor on the nanocarrier was an ultrasonic loading method, and the specific process parameters were: ultrasonic power 180 W, temperature 4° C., time 15 min, nanocarrier concentration The concentration of the chondrogenic differentiation growth factor GDF-5 was 0.25 wt %, and the concentration of the chondrogenic differentiation growth factor GDF-5 was 600 μM. After loading, the nanocarriers loaded with the osteogenic differentiation factor had a concentration of 0.05 wt % in the ColMA matrix. 3D printing was performed (light-proof conditions, nozzle aperture 200 μm, printing speed 20 mm / s, XY axis printing accuracy 0.01 mm, Z axis accuracy 0.004 mm, printing temperature 35°C, UV wavelength 405 nm, power 40 W, and curing time 5 min) to obtain an organic porous upper scaffold with a pore size of 200 μm.
[0043] 3) The upper surface of the lower support was polarized using plasma surface activation technology (nitrogen as plasma gas, nitrogen gas flow rate of 2.5 L / min, power of 300 W, output frequency of 30 kHz, distance between the device and the sample maintained at 15 mm, and treatment time of 10 min). The bonding surface of the upper and lower supports was then pre-wetted with a water-absorbing self-curing adhesive composed of polyethyleneimine and polyacrylic acid (addition amount was 100 mg / cm 2 ; Pre-wetting time is 20s), wherein the bonding surface of the inorganic magnesium alloy porous lower support needs to be coated with PBS solution for wetting;
[0044] 4) The upper and lower scaffolds were bonded (10 min), and the adhesive was aged at 4° C. for 60 min to obtain a metal gel composite osteochondral repair porous scaffold material based on heterogeneous double-layer bonding technology.
[0045] Compared with Comparative Example 1, this embodiment adds a ColMA organic porous upper scaffold. The upper and lower layers are closely bonded and will not fall off. After the extract was co-cultured with BMSCs for 7 days, the CCK-8 results showed that the cell survival rate was about 88.6%. Figure 2 This is the magnesium ion release curve of the porous scaffold material for repair in this example; after the scaffold material was irradiated and sterilized, it was implanted into a rabbit articular osteochondral defect model. After 8 weeks, hyaline cartilage was generated on the surface of the sample, and CT results showed that the subchondral bone regeneration was good, which together proved that the material has an excellent effect on the regeneration and repair of osteochondral. Figure 3 Middle a.
[0046] Example 2:
[0047] 1) Add magnesium alloy ball-milled powder with a particle size of 15 μm into the metal 3D printing device, set the laser beam spot diameter to 40 μm, the laser power to 400 W, the scanning rate to 600 mm / s, the scanning spacing to 100 μm, the nozzle diameter to 30 μm, the nozzle movement rate to 4 mm / s, the injection frequency to 1 kHz, the printing layer thickness to 40 μm, and the inorganic magnesium alloy porous lower layer support with a pore size of 300 microns by metal 3D printing technology; after printing, heat to 500 ° C at a heating rate of 10 ° C / min and sinter for 3 h, and cool to 40 ° C at a cooling rate of 5 ° C / min.
[0048] 2) Using ColMA with a degree of substitution of 60%, a 10 wt% ColMA / photoinitiator solution (LAP, 0.20 wt% photoinitiator) was prepared. 3D printing was performed (light-proof conditions, nozzle aperture of 200 μm, printing speed of 20 mm / s, printing accuracy of 0.01 mm in the X and Y axes, 0.004 mm in the Z axis, printing temperature of 35°C, UV wavelength of 405 nm, power of 40 W, and curing time of 5 min) to produce an organic porous upper scaffold with a pore size of 200 μm.
[0049] 3) The upper surface of the lower support was polarized using plasma surface activation technology (nitrogen as plasma gas, nitrogen gas flow rate of 2.5 L / min, power of 300 W, output frequency of 30 kHz, distance between the device and the sample maintained at 15 mm, and treatment time of 10 min). The bonding surfaces of the upper and lower supports were then pre-impregnated with a water-absorbing self-curing adhesive composed of polyethyleneimine and polyacrylic acid (addition amount of 100 mg / cm 2 ; Pre-wetting time is 20s), wherein the bonding surface of the inorganic magnesium alloy porous lower support needs to be coated with PBS solution for wetting;
[0050] 4) The upper and lower scaffolds were bonded (10 min), and the adhesive was aged at 4° C. for 60 min to obtain a metal gel composite osteochondral repair porous scaffold material based on heterogeneous double-layer bonding technology.
[0051] Compared with Example 1, this embodiment does not add cartilage differentiation-promoting growth factors and nanofillers loaded with cartilage differentiation-promoting growth factors into the upper porous scaffold. The upper and lower layers of the scaffold are closely bonded and will not fall off. The extract was co-cultured with BMSCs for 7 days, and the CCK-8 results showed that the cell survival rate was about 84.3%. After the scaffold material was irradiated and sterilized, it was implanted into a rabbit joint cartilage defect model for 8 weeks. The surface cartilage regeneration effect of the sample was poor, and some fibrous cartilage was generated. The CT results showed that there was a small amount of subchondral bone regeneration, indicating that the ColMA substrate and chondrogenic factors need to form a suitable physical and chemical microenvironment together to obtain an ideal cartilage repair effect. Figure 3 Middle b.
Claims
1. A method for preparing a porous scaffold material for repairing bone cartilage using a metal gel composite based on heterogeneous double-layer bonding technology, characterized in that: The following steps are involved: 1) The inorganic magnesium alloy porous lower bracket is obtained by metal 3D printing process; 2) using methacrylylated type I collagen (ColMA) / photoinitiator solution as a matrix, the matrix is mixed with a cartilage differentiation growth factor and loaded with a nanocarrier of the cartilage differentiation growth factor, and 3D printing is performed to obtain an organic porous upper scaffold; 3) using plasma surface activation technology to polarize the surface to be bonded of the lower support, and then using a water-absorbing self-curing adhesive to pre-wet the surfaces to be bonded of the upper and lower supports, wherein the surface to be bonded of the inorganic magnesium alloy porous lower support is coated with a PBS solution for wetting; 4) Bonding the upper and lower scaffolds, and then aging the adhesive to obtain a metal gel composite osteochondrium repair porous scaffold material based on heterogeneous double-layer bonding technology.
2. The method for preparing the metal gel composite osteochondrocyte repair porous scaffold material based on heterogeneous double-layer bonding technology according to claim 1, characterized in that: The pore size of the inorganic magnesium alloy porous lower support is 250-350 microns; The pore size of the organic porous upper support is 150-250 microns.
3. The method for preparing a porous scaffold material for repairing bone cartilage with metal gel composites based on heterogeneous double-layer bonding technology according to claim 2, characterized in that: Step 1) During the metal 3D printing process, selective laser melting is used, the oxygen content in the printing cavity is less than 0.2%, and a magnesium alloy ball-milled powder with a particle size of 15-25 μm is added to the metal 3D printing device, and the laser beam spot diameter is set to 40-60 μm, the laser power is 400-600 W, the scanning rate is 400-800 mm / s, the scanning spacing is 80-120 μm, the nozzle diameter is 30-40 μm, the nozzle movement rate is 3-6 mm / s, the injection frequency is 0.5-2 kHz, and the printing layer thickness is 40-60 μm; after printing is completed, it is heated to 500-550°C at a heating rate of 10-20°C / min and sintered for 2-3h, and cooled to 35-40°C at a cooling rate of 5-10°C / min.
4. The method for preparing a porous scaffold material for repairing bone cartilage with metal gel composites based on heterogeneous double-layer bonding technology according to claim 1, characterized in that: Step 2) In the ColMA / photoinitiator solution, the substitution degree of ColMA is 60-90%, the concentration is 10-20w%, the photoinitiator is one of LAP, Irgacure, and photoinitiator 2959, the concentration is 0.15-0.3wt%, and the solvent is PBS; The growth factors promoting cartilage differentiation are one or more of GDF-5, bFGF, FGF-10, Afgf and EGF, wherein the concentration of the growth factors directly mixed in the matrix is 160-220 μM, and the concentration of the growth factors promoting cartilage differentiation in the nanocarrier is 600-800 μM; The concentration of the nanocarrier loaded with cartilage differentiation promoting growth factors in the matrix is 0.05-0.1 wt %.
5. The method for preparing a porous scaffold material for repairing bone cartilage with metal gel composite based on heterogeneous double-layer bonding technology according to claim 4, characterized in that: In step 2), the preparation method of the nanocarrier loaded with the growth factor for promoting cartilage differentiation is as follows: the growth factor for promoting cartilage differentiation is combined with the nanocarrier by ultrasonic loading method, the ultrasonic power is 100-180W, the temperature is 4-10°C, the time is 5-15min, the concentration of the nanocarrier is 0.1-0.5wt%, and freeze-drying is performed after the loading is completed; The nanocarrier is one or more of ZIF-8, mesoporous manganese dioxide and mesoporous silica, preferably mesoporous silica.
6. The method for preparing a porous scaffold material for repairing bone cartilage with metal gel composites based on heterogeneous double-layer bonding technology according to claim 1, characterized in that: Step 2) During the 3D printing process, light-proof conditions were adopted, the nozzle aperture was 200-400 microns, the printing speed was 20-25 mm / s, the printing accuracy in the XY axis direction was 0.005-0.01 mm, the accuracy in the Z axis direction was 0.002-0.004 mm, the printing temperature was 30-35°C, the UV wavelength was 405 nm, the power was 20-40 W, and the curing time was 5-10 min.
7. The method for preparing a porous scaffold material for repairing bone cartilage with metal gel composite based on heterogeneous double-layer bonding technology according to claim 1, characterized in that: Step 3) In the plasma surface activation technology, nitrogen is used as plasma gas, the nitrogen gas flow rate is 2.5-4.5 L / min, the power is 200-450 W, the output frequency is 25-45 KHz, the distance between the device and the sample is maintained at 15-25 mm, and the processing time is 5-15 min; The water-absorbing self-curing adhesive is composed of polyethyleneimine and polyacrylic acid, and the addition amount is 50-100 mg / cm 2 ; The pre-wetting time is 10-20s.
8. The method for preparing the metal gel composite osteochondrocyte repair porous scaffold material based on heterogeneous double-layer bonding technology according to claim 1, characterized in that: In step 4), when bonding the upper and lower brackets, they need to be pressed to make them tightly bonded, and the bonding time is 5-15 minutes; during the aging process, the temperature is 4-10°C and the aging time is 40-80 minutes.
9. A metal gel composite osteochondrocyte repair porous scaffold material based on heterogeneous double-layer bonding technology, characterized in that: The method is adopted as described in any one of claims 1 to 8.
